A prototype of a novel cell phone application for tracking the vaccination coverage of children in rural communities. Issue 2 (November 2015) - Katib, Anas; Rao, Deepthi; Rao, Praveen; Williams, Karen; Grant, Jim
<x xml:space="preserve">Abstract</x> Highlights Jeev is a novel smartphone application for tracking the vaccination coverage of children. Jeev synergistically combines smartphones, QR codes, and national id cards. Jeev is scalable and power efficient.